Development of Mathematical Learning Test For Student Groups With Linguistic Intelligence - Nur Aqidah; Edi Prio Baskoro; Budi Manfaat (EduMa: Mathematics education learning and teaching, 2019)
This research is motivated by the availability of mathematical learning outcomes test instruments that are in accordance with the intelligence of students are inadequate. Therefore this study aims to develop the necessary tests. The test development follows the model proposed by Djemari Mardapi, which starts from the preparation of test specifications, writing test questions, testing the test, refining the test and assembling the test in full. Learning outcomes indicators refer to the syllabus in the 2013 curriculum and combine it with indicators of linguistic intelligence which then produce specific questions for groups of students with linguistic intelligence. The results of the field trials show that the test items developed have the ideal differentiation and difficulty level. The results of the application of the test on 27 students with linguistic intelligence showed that the mathematics learning outcomes of students of class VIII linguistic intelligence in SMP Negeri 7 Cirebon had reached KKM of 70.37%. Of the 27 students there were 3 students (11.11%) included in the less category, 5 students (18.52%) which included enough categories, 15 students (55.56%) which included good categories, and 4 students (14.81%) which included very good categories. From the results of the research, it was found that dominant students with linguistic intelligence who were given tests according to linguistic intelligence tended to obtain better mathematics learning outcomes than students with other intelligences who were given similar tests